Nothing Will Work Unless You Did: The Predictors of Postprison Employment - Duwe, Grant (Criminal justice and behavior, 2017)
Using multiple measures of postprison employment (finding a job, hours worked, and wages earned), we examined the predictors of postrelease employment outcomes for 15,111 prisoners released from Minnesota prisons between 2007 and 2010. Similar to existing research, employment rates for these former prisoners following their release from prison were higher than their preprison rates. Unlike previous research, however, we found the postprison employment rate did not return to preprison levels, but instead remained relatively flat after 2½ years. Moreover, the results showed the number of interventions in which prisoners participated significantly improved their chances of finding a job, hours worked, and wages earned. These effects were not confined to education and employment programming as positive results were also observed for other interventions such as substance abuse treatment, prison visitation, and cognitive-behavioral therapy.